1980
DOI: 10.1677/joe.0.0860371
|View full text |Cite
|
Sign up to set email alerts
|

Incubation in Mallards (Anas Platyrhynchos): Changes in Plasma Levels of Prolactin and Luteinizing Hormone

Abstract: The concentrations of prolactin and LH were measured in the plasma of male and female mallards (Anas platyrhynchos) during the breeding season. The concentration of prolactin in the female birds was low before and during egg-laying, increased threefold (P less than 0.001) during incubation and returned to basal levels immediately after the young were hatched. The drakes, which do not participate in incubation in this species, had fairly low prolactin levels throughout the breeding period; levels being slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 21 publications
6
36
0
Order By: Relevance
“…Although all species exhibit elevated circulating prolactin levels during incubation, prolactin levels drop at the time of hatching in many precocial species ( Fig. 2A, Etches et al, 1979;Sharp et al, 1979;Lea et al, 1981;Goldsmith and Williams, 1980;Goldsmith, 1982;Hall and Goldsmith, 1983) whereas they remain elevated during the chickrearing period in altricial species ( Fig. 2A, Dawson and Goldsmith, 1982;Hector and Goldsmith, 1985;Hall, 1986;Seiler et al, 1992;Lormée et al, 1999Lormée et al, , 2000Vleck et al, 2000;Riou et al, 2010;Angelier Fig.…”
Section: Prolactin Secretion and Reproductive Modesmentioning
confidence: 99%
“…Although all species exhibit elevated circulating prolactin levels during incubation, prolactin levels drop at the time of hatching in many precocial species ( Fig. 2A, Etches et al, 1979;Sharp et al, 1979;Lea et al, 1981;Goldsmith and Williams, 1980;Goldsmith, 1982;Hall and Goldsmith, 1983) whereas they remain elevated during the chickrearing period in altricial species ( Fig. 2A, Dawson and Goldsmith, 1982;Hector and Goldsmith, 1985;Hall, 1986;Seiler et al, 1992;Lormée et al, 1999Lormée et al, , 2000Vleck et al, 2000;Riou et al, 2010;Angelier Fig.…”
Section: Prolactin Secretion and Reproductive Modesmentioning
confidence: 99%
“…In combination with progesterone and estrogen, PRL reduces the latency of onset of maternal behavior (Bridges and Ronsheim, 1990). In several birds: bantams (Sharp et al, 1979(Sharp et al, , 1988, mallard ducks (Goldsmith and Williams, 1980), domestic ducks (Hall and Goldsmith, 1983), Japanese bantams (Zadworny et al, 1988) and native Thai chicken it has been shown that PRL concentrations are low before egg-laying, increase slightly during egg-laying, increase sharply before incubation and are maintained at high levels during incubation, and then decrease rapidly to basal levels immediately after hatching the young. Abundant evidence has linked maternal behavior in several avian species with increased PRL secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence has linked maternal behavior in several avian species with increased PRL secretion. High PRL levels are known to be associated with brooding behavior in chickens (Sharp et al, 1979(Sharp et al, , 1988Bedrak et al, 1981;Lea et al, 1981;Hoshino and Wakita, 1989), turkeys (Burke and Dennison, 1980;Proudman and Opel, 1981), mallard ducks (Goldsmith and Williams, 1980;Boos et al, 2007), and swans (Goldsmith, 1982). The studies in which broody chickens (Sharp et al, 1979), ducks (Goldsmith and Williams, 1980), and swans (Goldsmith, 1982) have been allowed to hatch and rear the young have shown that PRL concentrations decline at the end of the incubation period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially because of the harsh conditions under which this investigation was conducted, it is truly a remarkable accomplishment! Through serial samples drawn from birds under seminatural conditions endocrine investigations have been conducted on several anseriform species-Cygnus atratus (Goldsmith 1982), Anser indicus (Dittami 1981), Branta canadensis (Akeson and Raveling 1981), B. sandvicensis (R. S. Donham, P. C. Banko and D. S. Farner, unpublished), Anas platyrhynchos (Haase and Paulke 1975, Haase et al 1980, Goldsmith and Williams 1980, A. crecca , Aythya valisineria (Blum et al 1983). Because these investigations have been conducted under differing conditions with measurements of different hormones, and with different assay methods, generalizations are difficult.…”
Section: Endocrinology Of Feral Speciesmentioning
confidence: 99%